Differences between parents’ and paediatricians’ perceptions of mild respiratory infections in childhood: contrast study - Ortiz-Gonzalez, Luis; Delgado-Ojeda, Jesús; Guisado-Rasco, Mª Cinta; Santamaria-Orleans, Alicia; Coronel-Rodríguez, Cristobal (Frontiers in Public Health, 2024)
Mild respiratory infections are a common reason for consultation in paediatrics, both in the emergency department and in primary care clinics. These conditions, mostly viral and self-limiting, have a significant impact on the healthcare system, school and work absenteeism, and family routines. Despite being common and banal illnesses from a medical perspective, they involve a significant concern in families. The main objective of the Contrast Study was to compare the perceptions of parents and paediatricians regarding mild respiratory infections in childhood and their impact on family conciliation.Material and methods: Two online, cross-sectional surveys were conducted among Spanish paediatricians and parents with children aged 6 months to 12 years, involving 504 paediatricians and 1447 families, with questions on attitudes towards visits to the paediatric consultation, care burden of minor pathologies, work, and family conciliation, and treatment and prevention of these illnesses.Results: Results showed significant differences in paediatricians' and parents' perceptions in many aspects. According to 34.5% of pediatricians and 27% of parents, families regularly go to the pediatrician without a scheduled visit. Only 4% of parents report having self-medicated their child, while pediatricians raise this percentage significantly to 48%. Regarding the question: "it is normal for a child to have an average of 4 colds a year", only 25.5% of the surveyed families "strongly agree" unlike to 70.2% of pediatricians. 72.8% of pediatricians "strongly agree" with: "in my opinion, it is good for children to get sick to improve their immune system" reduced to 45.9% of parents. Consultations for minor pathologies represent a "high workload" for 60.9% of pediatricians, while this opinion is agreed by only 18.9% of the parents.Conclusions: Mild respiratory infections in childhood are perceived differently by paediatricians and parents. While paediatricians perceive them as a common and manageable phenomenon, parents tend to show higher concern and demand for medical attention. This study underlines the need to improve communication between paediatricians and parents to align perceptions, optimize the use of the health system resources, and improve the efficiency in the management of these common paediatric illnesses.